IMPLEMENTING ECONOMICORDER INTERVAL FOR MULTI ITEM TO REDUCE TOTAL INVENTORYCOST - Anastasia Lidya Maukar (Spektrum Industri, 2014)
Nowadays, Inventory management has become a major concern for company because it can bring value added. Inventory management focused on maintaining and managing the inventory level in order to fulfill the customer demand with the lowest cost. In retailing and wholesaling, multi items from the same supplier are jointly ordered. This mean, the order interval of each item must be the same. But, there are several manufacturing companies that have not achieving the optimum solution in inventory management for multi items. It leads the company to increase the total inventory cost. Most of them are caused by the improper order interval. Thus, appropriate of inventory management may reduce the total inventory cost. This research tried to identify this problem. The first step that should be done is by identifying the problems, scopes, and objectives of the research which aimed to minimize the inventory control management. Then collecting data and analyzing the supported data in inventory management. By using the total inventory cost analysis as a parameter in comparing the actual system and the proposal system. This research also used forecasting methodology in order to predicting the future demand. In the final section is by implementing the Economic Order Interval in ordering process for determining the optimum order interval. The result in this thesis show that the proposal system can reduce the total inventory cost over 21% from the current condition. Keywords : Inventory control and management, multi-item, Economic Order Interval, total inventory cost, forecasting.